2020
DOI: 10.2196/15976
|View full text |Cite
|
Sign up to set email alerts
|

How Geographical Isolation and Aging in Place Can Be Accommodated Through Connected Health Stakeholder Management: Qualitative Study With Focus Groups

Abstract: Background In remote areas, connected health (CH) is needed, but as local resources are often scarce and the purchasing power of residents is usually poor, it is a challenge to apply CH in these settings. In this study, CH is defended as a technological solution for reshaping the direction of health care to be more proactive, preventive, and precisely targeted—and thus, more effective. Objective The objective of this study was to explore the identity of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The emerging MHS include diagnostic services, preventive services, procedural services and other health-related services, which are performed on mobile applications or devices, greatly saving users' time and economic costs (Brownconnolly et al, 2014;Huvila et al, 2018). Furthermore, the global phenomenon of population aging makes people's medical health a common problem, especially in remote areas, which accelerates the development of e-health (Chen et al, 2020).…”
Section: Theoretical Background 21 Mobile Health Services and Protect...mentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging MHS include diagnostic services, preventive services, procedural services and other health-related services, which are performed on mobile applications or devices, greatly saving users' time and economic costs (Brownconnolly et al, 2014;Huvila et al, 2018). Furthermore, the global phenomenon of population aging makes people's medical health a common problem, especially in remote areas, which accelerates the development of e-health (Chen et al, 2020).…”
Section: Theoretical Background 21 Mobile Health Services and Protect...mentioning
confidence: 99%
“…And the mobility and flexibility of MHS have greatly improved the accessibility of medical services and overcome the shortcomings caused by the scarcity of medical resources (Kim et al, 2017;Chen, 2018). For example, due to the flexibility of time and space, Chen et al (2020) found that the use of e-health can achieve seamless patient care and clinical benefits by investigating the implementation of e-health from the perspectives of stakeholder management in remote locations. Although mobile medical services have a variety of advantages, their development also faces lots of challenges because of their innovativeness as a new application, especially for the elderly users (Zhang et al, 2017;Zhao et al, 2018;Waqas et al, 2021).…”
Section: Theoretical Background 21 Mobile Health Services and Protect...mentioning
confidence: 99%
“…Both of these frameworks include the enduser (e.g., food pantry clients) within the intervention development process, ensuring that the tools meet the needs of intended users [88]. In addition, stakeholder management and analysis frameworks provide valuable protocols for improving acceptability and usability [3,4]. Despite these frameworks, only 12 studies were performed in partnership with or led by food assistance programs.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile Health (mHealth) and digital application technology have revolutionized public health [1][2][3][4]. Digital interventions have been shown to successfully improve health behaviors, ranging from smoking cessation to diet [5,6] and health outcomes, including weight loss [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted/one-on-one feedback Targeted/one-on-one feedback seeks out individuals with specific knowledge, experience, or insights about a research topic, 28 who may be geographically distant or have other barriers to regular participation in groups. 29,30 As such, it may be particularly useful to engage traditionally underrepresented populations.…”
Section: Consortium-level Community/patient Stakeholder Groupsmentioning
confidence: 99%